2010
DOI: 10.1080/03601231003613609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methamidophos on the community structure, antagonism towardsRhizoctonia solani, andphlDdiversity of soilPseudomonas

Abstract: A microcosm incubation study using an aquic brown soil from northeast China (a Cambisol in the UN Food and Agriculture Organization FAO Soil Taxonomy) was conducted to examine the effects of different concentrations (0, 50, 150, and 250 mg kg(-1)) of methamidophos (O,S-dimethyl phosphoramidothioato) on Pseudomonas, one of the most important gram-negative bacteria in soil. Amplified ribosomal DNA restriction analysis (ARDRA) was performed to study the Pseudomonas community structure, an in vitro assay was made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…The prolonged or continued use of acephate and methamidophos in plant protection may lead to significant dermal exposure with an impact on cholinesterase, genotoxicity and cardiotoxicity activities (Farag et al, 2000;Spassova et al, 2000;Padungtod et al, 1998). Immense toxicity of acephate and methamidophos has been observed in environment including birds (Zinkl et al, 1981;Vyas et al, 1996), animals (Singh and Drewes, 1987), fishes (Szeto et al, 1979), soils and its microorganisms (Wu et al, 2010;Lo, 2010;Battu et al, 2009). Studies have revealed that acephate and methamidophos can persist on soils (Zhang et al, 2005;Battu et al, 2009), fruits and vegetables (Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010;Zhang et al, 2008), in dietary products (WHO, 2003(WHO, , 2005Nougade`re et al, 2012), cereal and other cash crops (Hiemstra & Kok, 2007;Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010).…”
Section: Mode Of Action and Toxicitymentioning
confidence: 98%
“…The prolonged or continued use of acephate and methamidophos in plant protection may lead to significant dermal exposure with an impact on cholinesterase, genotoxicity and cardiotoxicity activities (Farag et al, 2000;Spassova et al, 2000;Padungtod et al, 1998). Immense toxicity of acephate and methamidophos has been observed in environment including birds (Zinkl et al, 1981;Vyas et al, 1996), animals (Singh and Drewes, 1987), fishes (Szeto et al, 1979), soils and its microorganisms (Wu et al, 2010;Lo, 2010;Battu et al, 2009). Studies have revealed that acephate and methamidophos can persist on soils (Zhang et al, 2005;Battu et al, 2009), fruits and vegetables (Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010;Zhang et al, 2008), in dietary products (WHO, 2003(WHO, , 2005Nougade`re et al, 2012), cereal and other cash crops (Hiemstra & Kok, 2007;Antonious and Snyder, 1994;Bouchard and Lavy, 1982;Chuanjiang et al, 2010).…”
Section: Mode Of Action and Toxicitymentioning
confidence: 98%
“…The above observations indicated that the SinoChiral OJ column has a better enantioselective discrimination ability toward PCBs than the Chiralcel OD and Chiralpak IB columns under the chromatographic conditions considered. A previous study, which investigated chiral separation of PCBs on the Sino-Chiral OJ column using HPLC showed that only three PCBs could be baseline resolved [28], while baseline resolution of 14 PCBs was obtained on the Sino-Chiral OJ column by SFC. The observation may be ascribed to the fact that SFC has a higher diffusion coefficient and mass transfer rate than those of HPLC.…”
Section: Resultsmentioning
confidence: 98%
“…Este resultado está condizente com o maior número de isolados Gram-negativos neste experimento (Tabela 9). Caracterização macroscópica e microscópica das cepas isoladas em meio R2A.Os perfis de ARDRA baseados na especificidade dos sítios de digestão dos genes de rRNA 16s são biomarcadores úteis na análise da estrutura da comunidade das bactérias do solo e tem sido adotado como um método para quantificar a diversidade bacteriana nos solos contaminados por defensivos agrícolas e outro químicos(WU et al, 2010).…”
unclassified